Cellular Ingestible DNA Nanostructures for Biomedical Applications. Issue 1 (4th December 2022) - Xu, Rui; Li, Yujie; Zhu, Chenyou; Liu, Dongsheng; Yang, Yuhe R.
Abstract : Delivering functional substances across the cell membrane barriers has been a great challenge in biomedicine. Among various strategies to improve cellular uptake, DNA nanostructures, with different shapes and sizes, supply as suitable platforms for delivering a wide range of functional substances to cells. With great programmability, biocompatibility, and biostability, DNA nanostructure‐based delivery systems have shown and have succeeded in anticancer therapy, antibacterial treatment, gene editing, vaccine development, and stem cell bioengineering. Herein, the development and construction of various cellular ingestible DNA nanostructures are described, the loading strategies of functional substances are summarized, current biomedical applications are overviewed, and finally the remaining challenges and opportunities are discussed. Abstract : DNA nanostructure‐based delivery systems have shown and have succeeded in anticancer therapy, antibacterial treatment, gene editing, vaccine development, and stem cell bioengineering. Herein, the development and construction of various cellular ingestible DNA nanostructures are described, the loading strategies of functional substances are summarized, current biomedical applications are overviewed, and finally the remaining challenges and opportunities are discussed.